Curcumin and non-alcoholic fatty liver disease - Nasrin Sharifi; Somaye Kamarei; Hamed Mirzaei (مجله علوم پزشکی فیض (پیوسته))
Non-Alcoholic Fatty Liver Disease (NAFLD) is the most prevalent liver disorder, characterized by the excessive accumulation of fat in the liver due to causes other than heavy alcohol consumption. The exact etiology of NAFLD remains unclear. Currently, lifestyle modifications, including diet and exercise, are the primary strategies for the prevention and treatment of NAFLD. However, certain plant bioactive compounds may also offer potential benefits for NAFLD management with acceptable safety profiles. These herbal medicines appear to play a significant role in mitigating oxidative stress by reducing insulin resistance, decreasing fat accumulation in the liver, and interacting with hepatic fat metabolism. Turmeric (Curcuma longa), a perennial plant from the ginger family (Zingiberaceae), contains the active ingredient curcumin. With its polyphenol structure, curcumin has long been recognized as a home remedy for various ailments. Numerous studies indicate that curcumin possesses antimicrobial, anti-inflammatory, antioxidant, immune-regulating, nephroprotective, anti-cancer, hepatoprotective, and blood sugar-lowering properties through various signaling pathways and gene expression regulation. While substantial evidence from laboratory and animal studies supports the hepatoprotective effects of curcumin, the sole human study conducted in this area yielded inconclusive results. Therefore, this study aims to present a selection of definitive findings regarding the effects of curcumin/turmeric on NAFLD.